Bioinspired mono-component lignin endowing epoxy resin with simultaneously improving flame retardancy and mechanical properties. (November 2022) - Liu, Yuhan; Liu, Baijun; Sun, Zhaoyan; Zhang, Huiliang; Men, Yongfeng; Hu, Wei; Shao, Zhubao
Abstract: As an appropriate bio-based substance of flame retardant, lignin exhibits an increasing focus due to its environmental friendliness, high-efficiency charring, and renewable property. However, the conventional flame retardants containing lignin with high flame safety always confront with deterioration of mechanical properties of matrix. Here, a novel flame retardant (LMA) by assembling lignin with melamine and amino trimethyl phosphonic acid through electrostatic interaction was constructed. The LMA displayed excellent interfacial strength with epoxy resin resulting from the ring-opening reaction between rich hydroxyl group in LMA and epoxy resin (EP), thereby the tensile strength, impact strength and Young's modulus of EP-LMA7 increased by 17.9%, 53.7% and 25.7%, respectively. More importantly, EP-LMA7 passed the V-0 rating of UL-94 and the limiting oxygen index (LOI) value achieved 30.2%. Moreover, with respect to EP, the peak of heat release rate and the peak of smoke production rate of EP-LMA7 decreased by 72.3% and 77.5%, respectively. The detailed characterization illustrated that the excellent intumescent charring resulted in the satisfactory flame safety of EP. This work will further broaden the efficient utilization of lignin. Graphical abstract: Image 1 Highlights: Self-assembled modified lignin-based flame retardant (LMA) was prepared. With the 7 wt% addition of LMA, the heat release and smoke production of EP-LMA7 were greatly decreased. LMA improved the mechanical performance of EP simultaneously. EP-LMA7 passed the V-0 rating of the UL-94 test, which possessed a superb flame retardant performance.